2023
DOI: 10.1001/jamanetworkopen.2023.2371
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Financial Incentives and Default Options on Food Choices of Adults With Low Income in Online Retail Settings

Abstract: ImportanceDespite recent growth in online redemption of Supplemental Nutrition Assistance Program (SNAP) benefits, no previous work has tested the impact of economic and behavioral economic strategies on food purchasing behaviors in an online grocery retail setting among adults with low income.ObjectiveTo examine the extent to which financial incentives and default shopping cart options influence fruit and vegetable purchases.Design, Setting, and ParticipantsThis randomized clinical trial used an experimental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…16,124 Previous FIM interventions have at times had limited success in improving diet quality, despite generous incentives, and making those incentives more effective dollar for dollar, combining them with other behavioral strategies, will be an important priority. 71,55,125,127 We will systematically test various behavior change strategies that recognize the inherent difficulties those with food or nutrition insecurity face and that incorporate humancentered design to create programs that have a better chance of meeting people where they are and achieving successful engagement. [128][129][130][131][132][133] An important contribution of the initiative be developing common data platforms that facilitate FIM research.…”
Section: Plans and Methods For The Aha Fim Initiativementioning
confidence: 99%
See 1 more Smart Citation
“…16,124 Previous FIM interventions have at times had limited success in improving diet quality, despite generous incentives, and making those incentives more effective dollar for dollar, combining them with other behavioral strategies, will be an important priority. 71,55,125,127 We will systematically test various behavior change strategies that recognize the inherent difficulties those with food or nutrition insecurity face and that incorporate humancentered design to create programs that have a better chance of meeting people where they are and achieving successful engagement. [128][129][130][131][132][133] An important contribution of the initiative be developing common data platforms that facilitate FIM research.…”
Section: Plans and Methods For The Aha Fim Initiativementioning
confidence: 99%
“…62,69 Although some modeling studies have suggested potentially large benefits from produce prescription programs, 70 these estimates come with substantial uncertainty given that their underlying assumptions about the degree to which reductions in healthy food prices translate into increased consumption have not been borne out in recent trials. 71 A substantial limitation of the produce prescription approach is the exclusive focus on the consumption of fruits and vegetables. Cashlike FIM interventions may be more impactful if they incentivize not only fruit and vegetable purchasing but also other important components of healthy diets such as whole grains, legumes, and lean proteins.…”
Section: Current Landscape Of Fim Researchmentioning
confidence: 99%
“…Existing reviews of marketing practices in online grocers suggests that nudging interventions related to marketing and promotion, such as suggested food swaps for products with healthier characteristics than the ones selected by the shopper, food labeling, and default options, may improve the healthfulness of online food purchases [12,17]. In a recent randomized trial, the default option of a prefilled shopping cart with fruit and vegetable items led to a significant increase in fruit and vegetable purchases made online [164]. However, further research is needed to test various nudging interventions in realistic online settings.…”
Section: The Online Food Retail Landscapementioning
confidence: 99%
“…Pomeranz et al examined the feasibility of various national F/V subsidies in existing local programs and their population health outcome impacts and concluded a nationally mandated subsidy can help reduce diet-related chronic disease and U.S. health economic burdens (62). These programs should be broadly expanded in the 2023-24 Farm Bill and integrated into Electronic Benefits Transfer (EBT) modalities while broadly upscaling other innovative digital program administration and online grocery purchase options that work well for consumer preferences, such as the popular F/V 'double-bucks' formats (63)(64)(65). Ensuring a greater variety of access, ordering and delivery approaches with online modalities, sufficient Broadband infrastructure and retail hub access will be key to advancing innovative SNAP benefit participation and utilization, especially in rural areas featuring complex interactions between individual state, multi-state, federal and commerce networks (62).…”
Section: Policy Option 2 -Healthy Food Subsidies For F/vmentioning
confidence: 99%